The Effect of Product Quality, Price Affordability, and Brand Equity on Porang Rice Purchase Decisions Through Halal Awareness as a Moderating Variable - Dhealzy Rheynanda Syukrillah; Wahyu Santoso; Mirza Andrian Syah (Danadyaksa: Post Modern Economy Journal, 2026)
This study aims to analyze the influence of product quality, price affordability, and brand equity on purchase decisions of porang rice through halal awareness in Central Jakarta. Porang rice is an alternative food product with high fiber and low calorie content that has the potential to support food diversification in Indonesia. However, consumer acceptance of porang rice is still relatively varied and influenced by several marketing factors as well as halal considerations. This research used a quantitative approach with a survey method. Data were collected through questionnaires distributed to consumers who had knowledge or experience purchasing porang rice in Central Jakarta using purposive sampling. The variables analyzed consisted of product quality, price affordability, and brand equity as independent variables, halal awareness as a moderating variable, and purchase decision as the dependent variable. Data analysis was conducted using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) approach through SmartPLS software. The results showed that product quality, price affordability, and brand equity have a significant effect on purchase decisions. These findings indicate that marketing factors combined with halal awareness play an important role in influencing consumer purchasing decisions for porang rice in urban areas.